Laparoscopic Surgery for Focal-Form Congenital Hyperinsulinism Located in Pancreatic Head - Wen, Zhe; Wang, Jieqin; Liang, Qifeng; Chang, Xiaopan; Zhang, Wen; Niu, Huilin; He, Qiao (Frontiers in Pediatrics, 2022)
Background and Aims Congenital hyperinsulinism of infancy (CHI) is a rare condition that may cause irreversible severe neurological damage in infants. For children in whom medical management fails, partial or near-total pancreatectomy is then required according to the type of lesion. Currently, open surgery of near-total pancreatic head resection is a mature technique for the treatment of focal-form CHI located in the head of the pancreas, but a minimally invasive laparoscopic procedure has not been reported yet. The aim of this study was to verify the feasibility, safety, and efficacy of laparoscopic pancreatic head resection and Roux-en-Y pancreaticojejunostomy for focal-form CHI. Methods Two infants with persistent hypoglycemia and increased insulin levels were diagnosed with CHI and underwent laparoscopic near-total pancreatic head resection due to a suboptimal response to medical therapy and the likelihood of focal disease amenable to surgery. Clinical records, operative findings, and postoperative follow-up were collected and analyzed. Results The operative duration was 300–330 min, and the intraoperative blood loss was minimal. The duration of postoperative abdominal drainage was 4–5 days. Neither intra- nor postoperative abdominal complications occurred. Oral feeding was resumed 3–4 days after the operation, and the blood glucose level was gradually stabilized to within the normal range. Normal blood glucose was observed in both patients over a follow-up period of 3–6 months. Conclusions Laparoscopic pancreatic head resection and Roux-en-Y pancreaticojejunostomy can be considered a safe and effective procedure with minimal morbidity and excellent outcomes for the treatment of focal CHI in the head of the pancreas.